Immunity and lymphocytic-thrombocytic adhesion in community-aquired pneumonia - Yu A Vitkovskiy; Yu V Golodnykh; B I Kuznik; I D Likhanov; A V Solpov; Yu A Vitkovsky; Yu V Golodnykh; B I Kuznik; I D Likhanov; A V Solpov (Терапевтический архив, 2009)
Aim. To investigate immunity and lymphocytic-thrombocytic adhesion in pneumonia patients. Material and methods. The examination of 59 male patients with pneumonia aged 18-21 years included calculation of total leucocyte count, lymphocyte subpopulations, relative and absolute count of lymphocytic-thrombocytic aggregates (LTA), measurement of IgA, IgM, IgG concentrations. Results. Pneumonia patients have high count of leukocytes and low count of total and relative count of lymphocytes, low number of main lymphocytic subpopulations (CD4+, CD8+, CD16+, CD22+). Patients with uncomplicated pneumonia demonstrated high ability of lymphocytes for forming coaggregates with platelets. Patients with severe pneumonia complications may have either very high count of LTA (mean 403 ± 45.6) or very low (mean 42.6 ± 8.1). Percent of lymphocytes able to adhere to platelets (CD4+ with CD16+) in pneumonia is low. No correlation was found between LTA and the level of IgA, IgG, IgG. Conclusion. LTA is an objective indicator of cellular immunity status in pneumonia patients.